The quantitative proteomics analysis of multi-stage gastric mucosal lesions associated with Helicobacter pylori infection - Xiaoxi Huang; Jiamei Ma; Yening Xiao; Jing Pan; Qin Xu; Xifan Cao; Yongchao Liu; Xiang Yi; Fang Tian (PLoS ONE, 2026)
Background Helicobacter pylori ( H. pylori ) infection is the principal etiological factor for gastric cancer (GC), which ranks as the fourth leading cause of cancer-related mortality globally. Although the Correa cascade describes the stepwise progression from chronic gastritis to intestinal-type GC, the molecular events underlying this “inflammation-to-cancer” transition remain incompletely characterized. Objective This study aimed to delineate stage-specific proteomic alterations across H. pylori -associated gastric mucosal lesions and to identify candidate progression-associated biomarkers in GC. Methods Label-free quantitative proteomic analysis (LC-MS/MS) was performed on gastric tissue specimens from 22 patients stratified into four histopathological stages: H. pylori -negative chronic non-atrophic gastritis (HpN-CG), H. pylori -positive chronic non-atrophic gastritis (HpC-CG), H. pylori -positive chronic atrophic gastritis (HpC-CAG), and intestinal-type GC. Functional enrichment (GO, KEGG), temporal clustering (Mfuzz), and protein-protein interaction (PPI) network analyses were conducted. Key hub genes were externally assessed using GEPIA RNA-seq data from TCGA and GTEx. Results A total of 6,019 proteins were quantified. Differential expression analysis identified 771 DEPs between HpC-CG and HpN-CG, 101 DEPs between HpC-CAG and HpC-CG, and 535 DEPs between GC and HpC-CAG. Immune response pathways were up-regulated upon H. pylori infection, whereas oxidative phosphorylation was progressively suppressed throughout disease progression. Mfuzz clustering revealed that Cluster 4 ribosome-biogenesis proteins, including NIP7 and PDCD11 identified in the proteomic/PPI analysis, exhibited continuous up-regulation from precancerous stages to GC. External RNA-expression validation supported significant up-regulation of seven Cluster 4 hub genes, whereas Cluster 6 proteins did not show concordant transcript-level down-regulation. Conclusion This study provides a comprehensive proteomic landscape of H. pylori -driven gastric carcinogenesis. Cluster 4 ribosome-biogenesis proteins represent candidate progression-associated protein markers requiring further protein-level validation, while the progressive decline in oxidative phosphorylation underscores mitochondrial dysfunction as a hallmark of disease progression.